Photogrammetry as a Digital Tool for Joining Heritage Documentation in Architectural Education and Professional Practice - Irina Salagean-Mohora; Anamaria Andreea Anghel; Flaviu Mihai Frigura-Iliasa (Buildings, 2023)
Given the accelerated technological advance in all fields, vast knowledge of digital tools becomes mandatory for future interior designers and architects. Thus, experimenting with as many such methods and technologies must become a priority for the teaching process. Noticing a high demand for digitalization during the COVID-19 pandemic, the Polytechnic University of Timisoara has decided to encourage the implementation of digital teaching throughout disciplines, preparing students for their future careers. Photogrammetry as a study method, among others, has the potential to outrank traditional documentation techniques currently applied in architectural education and practice. The presented research was divided into two main phases: an educational, experimental workshop and a project restoration application. After learning, testing, and refining the close-range photogrammetry workflow, the authors and students took the best practices and applied them to an ongoing facade restoration project in Timisoara, scanning original and restored plaster ornaments and finally 3D printing one of the models. The article aims to show that, unlike traditional teaching methods, using photogrammetry as a documentation process creates a coherent link between theoretical education and restoration practice. Consequently, the exercise brings students closer to the applicable side of their careers through a contemporary digital technique.